Propofol-induced unresponsiveness is associated with impaired feedforward connectivity in cortical hierarchy. (November 2018) - Sanders, R.D.; Banks, M.I.; Darracq, M.; Moran, R.; Sleigh, J.; Gosseries, O.; Bonhomme, V.; Brichant, J.F.; Rosanova, M.; Raz, A.; Tononi, G.; Massimini, M.; et al.
Abstract: Background: Impaired consciousness has been associated with impaired cortical signal propagation after transcranial magnetic stimulation (TMS). We hypothesised that the reduced current propagation under propofol-induced unresponsiveness is associated with changes in both feedforward and feedback connectivity across the cortical hierarchy. Methods: Eight subjects underwent left occipital TMS coupled with high-density EEG recordings during wakefulness and propofol-induced unconsciousness. Spectral analysis was applied to responses recorded from sensors overlying six hierarchical cortical sources involved in visual processing. Dynamic causal modelling (DCM) of induced time–frequency responses and evoked response potentials were used to investigate propofol's effects on connectivity between regions. Results: Sensor space analysis demonstrated that propofol reduced both induced and evoked power after TMS in occipital, parietal, and frontal electrodes. Bayesian model selection supported a DCM with hierarchical feedforward and feedback connections. DCM of induced EEG responses revealed that the primary effect of propofol was impaired feedforward responses in cross-frequency theta/alpha–gamma coupling and within frequency theta coupling (F contrast, family-wise error corrected P <0.05). An exploratory analysis (thresholded at uncorrected P <0.001) also suggested that propofol impaired feedforward and feedback beta band coupling. Post hoc analyses showed impairments in all feedforward connections and one feedback connection from parietal to occipital cortex. DCM of the evoked response potential showed impaired feedforward connectivity between left-sided occipital and parietal cortex (T contrast P =0.004, Bonferroni corrected). Conclusions: Propofol-induced loss of consciousness is associated with impaired hierarchical feedforward connectivity assessed by EEG after occipital TMS.